Fourier transform spectrometer measurements of column CO2 at Sodankylä, Finland - Kivi, Rigel; Heikkinen, Pauli (Geoscientific Instrumentation, Methods and Data Systems, 2016)
Fourier transform spectrometer (FTS) observations at Sodankylä, Finland (67.4° N, 26.6° E) have been performed since early 2009. The FTS instrument is participating in the Total Carbon Column Observing Network (TCCON) and has been optimized to measure abundances of the key greenhouse gases in the atmosphere. Sodankylä is the only TCCON station in the Fennoscandia region. Here we report the measured CO2 time series over a 7-year period (2009–2015) and provide a description of the FTS system and data processing at Sodankylä. We find the lowest monthly column CO2 values in August and the highest monthly values during the February–May season. Inter-annual variability is the highest in the June–September period, which correlates with the growing season. During the time period of FTS measurements from 2009 to 2015, we have observed a 2.2 ± 0.2 ppm increase per year in column CO2. The monthly mean column CO2 values have exceeded 400 ppm level for the first time in February 2014.